Pengering Ekonomis Untuk Optimalisasi Kapasitas Produksi Rengginan - Roby Syaiful Ubed; Taufik Raharjo; Ambang Aries Yudanto (Universitas Lancang Kuning, 2020)
The purpose of this service is to make a small scale dryer for Micro, Small and Medium Enterprises (MSMEs). This tool will help optimize the production process, to increase partner income. This tool is made with materials that are economical and easily obtained by partners. The method of carrying out community service activities is divided into three stages, namely the identification of problems and action plans, preparation, and implementation of activities. The results of the implementation of community service activities can be concluded that this activity has been able to have a positive impact on the process of inorganic production. This tool needs to be improved by adding a thermostat to measure the appropriate temperature in product drying and can set the time automatically. The accuracy of the effectiveness of this tool needs to be done with laboratory tests to test the level of water content, sensory tests, and texture tests. These tests are conducted so that production activities no longer use the feelings of partners in measuring the desired results.